Measurements of low-pT electrons from semileptonic heavy-flavour hadron decays at mid-rapidity in pp and Pb-Pb collisions at √sNN=2.76TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; et al. (Journal of high energy physics, 2018)
Transverse-momentum (pT) differential yields of electrons from semileptonic heavy-flavour hadron decays have been measured in the most central (0-10%) and in semi-central (20-40%) Pb-Pb collisions at sNN−−−√=2.76sNN=2.76 \sqrt{s_{NN}}=2.76 TeV. The corresponding production cross section in pp collisions has been measured at the same energy with substantially reduced systematic uncertainties with respect to previously published results. The modification of the yield in Pb-Pb collisions with respect to the expectation from an incoherent superposition of nucleon-nucleon collisions is quantified at mid-rapidity (|y| < 0.8) in the pT interval 0.5-3 GeV/c via the nuclear modification factor, RAA. This paper extends the pT reach of the RAA measurement towards significantly lower values with respect to a previous publication. In Pb-Pb collisions the pT-differential measurements of yields at low pT are essential to investigate the scaling of heavy-flavour production with the number of binary nucleon-nucleon collisions. Heavy-quark hadronization, a collective expansion and even initial-state effects, such as the nuclear modification of the Parton Distribution Function, are also expected to have a significant effect on the measured distribution. Open image in new window